(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
The article examines the socio-economic situation of Karakalpakstan in 1985–1990. Based on archival documents, it analyzes the outcomes of the social reforms during the "perestroika" period. Initiated by Gorbachev’s leadership, these reforms failed to address the socio-economic and living conditions of the population, especially in rural areas, and did not bring qualitative changes to the economic foundations of social life. The study explores key issues such as the formation of the socio-political climate, demographic trends, healthcare quality and funding, and population income levels. A historical-comparative analysis helps identify trends and factors that highlight the study’s relevance to contemporary developments.